Theoretical and methodological approaches to identifying deep accumulations of oil and gas in oil and gas basins of the Russian Federation - Prischepa, O. M.; Kireev, S. B.; Nefedov, Yu. V.; Martynov, A. V.; Lutsky, D. S.; Krykova, T. N.; Sinitsa, N.; Xu, Ruiming (Frontiers in Earth Science, 2023)
A large number of oil and gas accumulations at deep and ultra-deep depths, recently revealed in the world due to the development of drilling technologies, forces a revision of theoretical ideas on many issues, including conditions of oil and gas formation and hydrocarbon conservation in zones of high pressures and temperatures, as well as evaluating the possibility of conservation and formation of reservoirs. Among the most discussed, in this regard, are the issues determining the processes and rate of oil and gas formation at deep and ultra-deep depths, which differ significantly from those at small and medium depths: Thermobaric conditions responsible for the possibility of formation, phase distribution and conservation of hydrocarbons, geochemical indicators—type of kerogen, and its transformation, responsible for the phase distribution and staging of generation peaks—lithological composition of kerogen-bearing strata—the rate and scale of dip and uplift and the timing of exposure to high temperatures—the formation of overlapping saline strata and the presence of deep conductive faults that significantly affect temperature and pressure gradients. Analysis of the influence of the above factors on the prospects of deep-lying complexes taking into account new studies and achievements, mainly in the sedimentary basins of China (Tarim, Jungar, Ordos, Sichuan), the Gulf of Mexico and offshore Brazil (Santos) allowed typifying the sedimentary basins and major depressions of Russia, with the allocation of areas with high and ultra-low depth potential for hydrocarbon studies. Thermobaric and historical and geological criteria have been developed and a methodology for detailed study of promising areas has been proposed, including a complex of geochemical studies of hydrocarbons, extracts of bitumoids (pyrolytic, chromatographic) and lithological and petrophysical core studies aimed at assessing the prospects of oil and gas content of deep complexes in Russian sedimentary basins and the subsequent localization of the most promising areas for deep drilling.